Effect of substituted gelling agents from pomegranate peel on colour, textural and sensory properties of pomegranate jam. (15th January 2018) - Abid, Mouna; Yaich, Héla; Hidouri, Hayfa; Attia, Hamadi; Ayadi, M.A.
Highlights: Pomegranate jams were prepared with different amounts of sugar and LM pectin. Colour, texture and overall aceptability of pomegranate jams were studied. The formulation contaning 30% sugars and 0.2% pectin was the most appreciated. Commercial pectin was substituted by other gelling agents from pomegranate peel. A pomegranate peel based-jam exhibited similar acceptability to the reference jam. Abstract: A series of pomegranate jams were prepared from a Tunisian ecotype (Tounsi) with different amounts of sugar (10, 20 and 30%) and low-methoxylated pectin (0.2, 0.7 and 1.2%). The most appreciated formulation was that contaning 30% sugars and 0.2% pectin. Then, commercial pectin was substituted by other gelling agents (pomegranate peel powders dried at 50 °C vs lyophilized, pectin and fibre extracted from pomegranate peel) for the preparation of pomegranate peel-based jams. The elaborated jams were evaluated for physichochemical, colour, texture and sensory characteristics. Results revealed that the jam (JPP2) elaborated with 0.2% pectin extracted from pomegranate peel exhibited similar overall acceptability to that prepared with commercial pectin. However, it was more acceptable than other pomegranate peel-based jams, which was related to a better appreciation of sweetness and colour. According to the colour and texture measurements, this sample (JPP2) was more reddish and less firm than other samples.